2014
DOI: 10.2118/163354-pa
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of Voidage-Replacement Ratio in Well-Placement Optimization

Abstract: Determining the optimum location of wells during waterflooding contributes significantly to efficient reservoir management. Often, the voidage-replacement ratio (VRR) and net present value (NPV) are used as indicators of performance of waterflood projects. In addition, VRR is used by regulatory and environmental agencies as a means of monitoring the impact of field-development activities on the environment, whereas NPV is used by investors as a measure of profitability of oil and gas projects. Over the years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…3 is that for rand/1, the bigger N , the worse the result (see Config. [1][2][3][4]. For the current-to-best/1 strategy, the increase in N considerably improved the solutions for Config.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…3 is that for rand/1, the bigger N , the worse the result (see Config. [1][2][3][4]. For the current-to-best/1 strategy, the increase in N considerably improved the solutions for Config.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study was presented by [2] using CMA-ES and DE to solve the multi-objective optimization problem by manually weighting NPV and VRR, resulting in a singleoptimization problem. They concluded that CMA-ES outperformed DE for the majority of experiments, but that DE also obtained high-quality solutions.…”
Section: Literature Reviewmentioning
confidence: 97%
See 3 more Smart Citations